(untitled) (Eurasian Research Bulletin, 2026)
Preschool age is a period of active mental development, during which the foundations of a child’s personality, cognitive, and social skills are formed. Studying the relationship between attention and self-regulation in older preschool-aged children is a crucial aspect of child development. Attention allows a child to effectively perceive information and focus on tasks, while self-regulation helps control their emotions and, in the future, their learning. (Since play and learning are the primary activities in preschool, they have their own characteristics, and learning activities are related to the learning activities that are dominant in primary school age.) and actions. Their harmonious development lays the foundation for future success in learning and socialization. The ability to sustain attention for long periods and switch from one task to another directly depends on the level of selfregulation, which helps the child control their behavior and emotional state. The ability to manage attention and control one’s behavior is also important for a child’s social adaptation. Children who are able to focus on communication, listen to others, and regulate their emotional reactions integrate more easily into groups and interact better with peers and adults. This is especially important in preschool settings, where the development of social skills plays a crucial role in overall emotional and cognitive development